Non-invasive methods in the identification of hydrological ecosystem services of a tropical isolated wetland (Brazilian study case) - Casagrande, Matheus Felipe Stanfoca [UNESP]; Furlan, Lucas Moreira [UNESP]; Moreira, César Augusto [UNESP]; Rosa, Fernanda Teles Gomes [UNESP]; Rosolen, Vania [UNESP] (Elsevier, 2021)
In Brazil, since 2013 the Southeast region has been dealing with recurrent hydric stress resulted from the prolongation of the dry season, whose tendency is to be more dramatic in the function of climate change. The situation is more critical in some areas, including Cordeirópolis, projecting a reduction of 50%–100% in water availability in the next 15 years, demanding urgency in water availability-use balance. Considering the significant presence of small Geographic Isolated Wetlands (GIW) in the region, it is crucial the recognition of the link between wetlands and hydrology in the catchment since these ecosystems store rainwater and can act as aquifer recharger zones. The objective of this study is to evaluate the effectiveness of non-invasive methods, such as UAV-mapping and DC resistivity, and low-invasive (in situ hydraulic conductivity) to unveil the hydrological ecosystem services of a GIW in terms of surface and groundwater. From the high-resolution orthomosaic and digital elevation model, three compartments were qualified and quantified; (i) current wetland, (ii) Flooding area and, (iii) Potential wetland expansion. From the DC resistivity, the interaction between surface water and groundwater was identified, indicating the presence of a shallow saturated only beyond the perimeter of the current wetland as a possible result of land-use conversion or climate change. In addition, the local igneous intrusion comprises the connection between shallow/surface waters and deep aquifers made by fractures. Thus, the association of both methods showed high applicability concerning the identification of GIW superficial hydrological functions (UAV) and the system's subsurface dynamic (DC resistivity).
Keywords: aquifer; DC resistivity; electrical resistivity tomography; hydraulic conductivity; Unmanned Aerial Vehicle